Self-Concept in Postmenopausal Women: A Qualitative Study - Sharareh Bagheri; Ghobad Moradi; Samad Hamidi; Samrand Saeedi; Ameneh Hosaini; Jahanbakhsh Yousefi (Hamadan University of Medical Sciences, 2019)
Aims: Aging is associated with a phenomenon of menopause in women that is a very broad concept due to the coincidence with the appearance of aging symptoms. Menopause may affect women's quality of life and especially their health. The aim of this study was to explain the self-concept of postmenopausal women. Participants & Methods: The present study is a qualitative phenomenological research that was conducted among 23 menopausal women referred to Sanandaj health clinics in 2018 using semi-structured in-depth interviews. Participants were selected by purposive sampling method. Sampling continued until having achieved informational redundancy or saturation. The data were analyzed using MAXQDA 10 software and according to van Manen's six steps to guide phenomenological research. Findings: Five main themes were identified: intellectual ability, occupational efficiency, physical attractiveness, social skills, and virtues/vices, which is consistent with Beck self-concept test. In addition, the theme "physical health" was extracted from the participants' statements which are not part of the Beck test. Conclusion: Postmenopausal women, with the exception of intellectual ability and occupational efficacy, have problems in other themes such as physical attractiveness, social skills, and exercise, mood, and physical problems, which indicates inappropriate self-concept after menopause.